A Review of Societyâs Behaviour Towards Land Management of Susceptible Area to Landslide in Pekuncen, Banyumas - Suwarno, Suwarno; Sartohadi, Junun; Sunarto, Sunarto; Sadharto, Djarot (Forum Geografi, 2016)
Land management is a manifestation of the societyâs behaviour in utilizing the land. The objective of the research was to examine the effect of education level, income, land tenure, knowledge, and information input on the societyâs behaviour in managing the area susceptible to landslide in Pekuncen sub-district, Banyumas district.Â Â  The method of this research was survey by employing questionnaire to collect field data. The variable comprised of the data of education level, income, land tenure, knowledge, and information input.. Stratified random sampling was applied to determine the samples of the research. The area susceptibility classÂ  was considered as the strata in which each stratum consisted of 40 family heads as the respondents. The data analysis applied statistical test of multi-regression. Research area was divided into three classes of landslide susceptibility comprising of low, medium, and high class. Education level, income, land tenure, knowledge, and information input significantly influenced the societyâs behaviour dealing with land management (determination co-efficiency (RÂ²) was 69.9 %). It occurred in the area of medium susceptibility class. Information input (regression coefficient/(beta) = 0.817) was the most influential predictor of societyâs behaviour in land management located in the low susceptibility class. From this research, it was expected that the description about the factors that influenced the societyâs behaviour in managing the landslide-prone area would be a valuable reference in preventing landslide in those areas.